2008
DOI: 10.1017/s0954579408000412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early intervention on EEG power and coherence in previously institutionalized children in Romania

Abstract: Two groups of Romanian children were compared on spectral power and coherence in the electroencephalogram (EEG) in early childhood. One group consisted of previously institutionalized children who had been randomly assigned to a foster care intervention at a mean age of 23 months. The second group had been randomized to remain in institutional care. Because of a policy of noninterference, a number of these children also experienced placement into alternative family care environments. There were minimal group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
120
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 41 publications
15
120
1
1
Order By: Relevance
“…Subsequent studies of brain functioning have involved electroencephalography (EEG) and imaging studies. Institutional rearing appears to result in reduced electrical activity in higher frequencies and increased electrical activities in lower frequencies (Marshall et al, 2004(Marshall et al, , 2008Tarullo et al, 2011), but for children placed with families before 24 months, Vanderwert et al (2010) demonstrated normalization of brain functioning.…”
Section: Inadequate Inputmentioning
confidence: 99%
“…Subsequent studies of brain functioning have involved electroencephalography (EEG) and imaging studies. Institutional rearing appears to result in reduced electrical activity in higher frequencies and increased electrical activities in lower frequencies (Marshall et al, 2004(Marshall et al, , 2008Tarullo et al, 2011), but for children placed with families before 24 months, Vanderwert et al (2010) demonstrated normalization of brain functioning.…”
Section: Inadequate Inputmentioning
confidence: 99%
“…While there are myriad reasons for this low social mobility, we argue that reductions in fundamental auditory neural function may play a part. Because auditory disorders run in families (e.g., Maziade et al, 2000), auditory neural acuity may be transmitted from one generation to the next by genetic mechanisms. Yet, our study emphasizes that auditory neural acuity may also reflect the auditory environment that is shared between mother and child.…”
Section: Auditory Function and Social Mobilitymentioning
confidence: 99%
“…We predicted that adolescents with lower maternal education (no postsecondary education) would have lower literacy levels and working memory ability (Noble et al, 2007;Evans and Schamberg, 2009), coupled with weaker brainstem function than schoolmates with higher maternal education. This weakening, we posited, would translate into more inconsistent ABRs (Hornickel and Kraus, 2013), less robust responses to the input signal (Banai et al, 2009), and an altered resting brain state (Otero, 1997;Tomarken et al, 2004;Marshall et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…on early communication and language and speech development The development of children raised in institutionalized settings has been repeatedly studied , e.g. in the framework of The Bucharest Early Intervention Project [18,25,[31][32][33][34].…”
Section: Shared Characteristics Of Socially Deprived Subjects and Chimentioning
confidence: 99%